Law Enforcement Against the Criminal Acts of Forgery and or Placing False Information Into Authentic Deeds - Gatot Efrianto (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The Republic of Indonesia is a state of law (rechtstaats), so anyone who commits a crime must be held accountable for their actions through the legal process. Law enforcement implies that a crime is an act that is prohibited by a rule of law, where the prohibition is accompanied by a threat (sanction) in the form of a certain criminal penalty as its responsibility. The concept of a state of law is one that truly upholds human rights and guarantees citizens with their positions in law and government without exception, while to guarantee obedience and compliance with the law is in the hands of all citizens. Authentic deed in English (authentic deed), in Dutch (authentieke akte van), the philosophical basis that an authentic deed is found in: Legal considerations of Law No. 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning the Position of Notary and regulated in Article 1868 of the Civil Code (Civil Code) which states that